The enhanced expression of genes encoding diguanylate cyclases under cold stress contributes to the adhesion and biofilm formation of Shewanella putrefaciens WS13 - Xiong, Ruheng; Yan, Jun; Mei, Jun; Ye, Jingxin; Xie, Jing (Frontiers in Nutrition, 2022)
Shewanella putrefaciens is a special spoilage bacterium of seafood during cold storage, which is easy to form biofilm and bring serious hazard to the seafood quality. The life cycle of biofilm starts after bacterial adhesion, which is essential for the formation and development of biofilm. As a ubiquitous second messenger in bacteria, c-di-GMP regulates the conversion between bacterial planktonic state and biofilm state. In this study, the adhesion and biofilm formation of S. putrefaciens WS13 under 4 °C were compared to those under 30 °C. Results showed that the swarming mobility of S. putrefaciens WS13 was weaker under 4 °C, however, the adhesive force under 4 °C was 4-5 times higher than that under 30 °C. The composition of biofilm under 4 °C was similar to that under 30 °C, but the biofilm biomass, extracellular polysaccharides and extracellular proteins were 2.5 times, 3 times, and 1.6 times more than those under 30 °C, respectively. The level of c-di-GMP in S. putrefaciens WS13 under 30 °C was no more than half of the level of c-di-GMP in the corresponding growth stage under 4 °C. The results of quantitative real-time PCR analysis also showed that the expression of genes encoding diguanylate cyclases significantly enhanced under 4 °C than that under 30 °C. S. putrefaciens WS13 adapted to the cold stress by enhancing the expression of genes encoding diguanylate cyclases to promote bacterial adhesion and biofilm formation. This study provides a theoretical foundation for the research on the cold adaptation mechanism of specific spoilage bacteria of seafood based on c-di-GMP, and also provides a new idea to control seafood quality from the perspective of microbial molecular biology.